Abnormal urodynamic changes in post-upper urinary tract dysfunction in ureteral obstruction rat models - Liu, Xin; Li, Xing; Liao, Limin (Frontiers in Physiology, 2024)
This study investigated changes in upper urinary tract urodynamics (UUTU) after upper urinary tract dysfunction (UUTD). The UUTD model was induced through unilateral ureteral obstruction. To measure the renal pelvis volume, and resting pressure. Ureteral electromyography(EMG) and in situ ureteral constriction experiments were performed. Ureteral tissue was obtained for HE and masson staining, IF staining and IHC research to explore the distribution of Piezo1, and the expression of Piezo1 was studied using Western blotting. The study showed that the renal pelvis volumes and the renal pelvis resting pressures gradually increased post surgery in the experimental group. The degree of ureteral tissue edema, cell necrosis and fibrosis gradually increased. The maximum contraction force and frequency of ureter in the experimental group post surgery were significantly higher than in the sham group. Western blotting showed that the expression intensity of Piezo1 gradually increased and was significantly higher than in the sham group. Further analysis of each sub-layer of the ureter revealed that Piezo1 was highly expressed in the urothelium layer, followed by the suburothelium layer, and had low expression in the smooth muscle cell layer. The study observed that morphological and electrophysiological changes in the upper urinary tract may be important mechanisms of abnormal UUTU. Increased expression of the Piezo1 may be a new molecular mechanism of abnormal urodynamics after UUTD.